Acute intoxication with diisopropylfluorophosphate promotes cellular senescence in the adult male rat brain - Tsai, Yi-Hua; González, Eduardo A.; Grodzki, Ana C. G.; Bruun, Donald A.; Saito, Naomi H.; Harvey, Danielle J.; Lein, Pamela J. (Frontiers in Toxicology, 2024)
Acute intoxication with high levels of organophosphate (OP) cholinesterase inhibitors can cause cholinergic crisis, which is associated with acute, life-threatening parasympathomimetic symptoms, respiratory depression and seizures that can rapidly progress to status epilepticus (SE). Clinical and experimental data demonstrate that individuals who survive these acute neurotoxic effects often develop significant chronic morbidity, including behavioral deficits. The pathogenic mechanism(s) that link acute OP intoxication to chronic neurological deficits remain speculative. Cellular senescence has been linked to behavioral deficits associated with aging and neurodegenerative disease, but whether acute OP intoxication triggers cellular senescence in the brain has not been investigated. Here, we test this hypothesis in a rat model of acute intoxication with the OP diisopropylfluorophosphate (DFP). Adult male Sprague-Dawley rats were administered DFP (4 mg/kg, s.c.). Control animals were administered an equal volume (300 µL) of sterile phosphate-buffered saline (s.c.). Both groups were subsequently injected with atropine sulfate (2 mg/kg, i.m.) and 2-pralidoxime (25 mg/kg, i.m.). DFP triggered seizure activity within minutes that rapidly progressed to SE, as determined using behavioral seizure criteria. Brains were collected from animals at 1, 3, and 6 months post-exposure for immunohistochemical analyses of p16, a biomarker of cellular senescence. While there was no immunohistochemical evidence of cellular senescence at 1-month post-exposure, at 3- and 6-months post-exposure, p16 immunoreactivity was significantly increased in the CA3 and dentate gyrus of the hippocampus, amygdala, piriform cortex and thalamus, but not the CA1 region of the hippocampus or the somatosensory cortex. Co-localization of p16 immunoreactivity with cell-specific biomarkers, specifically, NeuN, GFAP, S100β, IBA1 and CD31, revealed that p16 expression in the brain of DFP animals is neuron-specific. The spatial distribution of p16-immunopositive cells overlapped with expression of senescence associated β-galactosidase and with degenerating neurons identified by FluoroJade-C (FJC) staining. The co-occurrence of p16 and FJC was positively correlated. This study implicates cellular senescence as a novel pathogenic mechanism underlying the chronic neurological deficits observed in individuals who survive OP-induced cholinergic crisis.